Association between post-percutaneous coronary intervention bivalirudin infusion and net adverse clinical events: a post hoc analysis of the GLOBAL LEADERS study. Issue 1 (9th December 2019) - Chang, Chun Chin; Chichareon, Ply; Modolo, Rodrigo; Takahashi, Kuniaki; Kogame, Norihiro; Tomaniak, Mariusz; Gao, Chao; Royaards, Kees-Jan; Cequier, Angel; Oldroyd, Keith; Steg, Philippe Gabriel; Hamm, Christian; et al.
Abstract: Aims: The efficacy and safety of continued bivalirudin infusion after percutaneous coronary intervention (PCI) remains uncertain. We sought to investigate the association between post-PCI bivalirudin infusion and the risk of net adverse clinical events (NACE) at 30 days. Methods and results: In the GLOBAL LEADERS study, all patients who received bivalirudin during PCI were categorized according to the use of bivalirudin infusion after the procedure. The primary endpoint of the present analysis was NACE [a composite of all-cause death, any stroke, any myocardial infarction, all revascularization, and bleeding assessed according to the Bleeding Academic Research Consortium (BARC) criteria Type 3 or 5] at 30 days. The key safety endpoint was BARC Type 3 or 5 bleeding and definite stent thrombosis. Of 15 968 patients, 13 870 underwent PCI with the use of bivalirudin. In total, 7148 patients received continued bivalirudin infusion after procedure, while 6722 patients received standard care. After propensity score covariate adjustment, the risk of NACE did not significantly differ between two treatments after PCI [continued bivalirudin infusion vs. no bivalirudin infusion: 3.2% vs. 3.1%, adjusted hazard ratio (aHR) 1.35, 95% confidence interval (CI) 0.99–1.84, P = 0.06] nor the BARC Type 3 or 5 bleeding (0.7% vs. 0.7%, aHR 0.89, 95% CI 0.44–1.79; P = 0.743) and definite stent thrombosis (0.5% vs. 0.3%, aHR 1.71, 95% CI 0.77–3.81, P = 0.189). However, continued bivalirudin infusion was associated with an increased risk of NACE and definite stent thrombosis in ST-elevation myocardial infarction (STEMI) patients. Conclusion: In an all-comers population undergoing PCI, there was no significant difference in the risk of NACE at 30 days between continued bivalirudin infusion vs. no bivalirudin infusion after procedure but continued bivalirudin infusion was associated with a higher risk of NACE in STEMI patients when compared with no infusion.